The legal construction of migrant work relations: precarious status, hyper-dependence and hyper-precarity - Zou, M (2014)
This thesis is concerned with the ways in which the laws and policies governing labour migration shape the relationship between migrant workers, employers, and labour markets in advanced industrialised countries. Specifically, it elucidates the intersections of immigration and labour market regulatory norms, structures, and processes that have salient implications for migrants’ work relations. The notions of ‘hyper-dependence’ and ‘hyper-precarity’ are developed as the main analytical and normative lenses in this thesis for examining the particular vulnerabilities associated with migrants’ precarious statuses under contemporary labour migration regimes. Hyper-dependence refers to an acute dependence that transcends the immediate context of an employment relationship, where other aspects of a worker’s life critically depend on that employer. For migrant workers, hyper-dependence may arise where their legal statuses is tethered to a specific employer sponsorship, accompanied by other de jure and de facto restrictions on their labour mobility. Hyper-precarity seeks to capture the multifaceted insecurities and uncertainties in migrants’ work relations and their broader migration projects, which are linked to their exclusion, in law and in practice, from a wide array of social, economic, and civil rights in the host state. Engaging with the various and often competing goals and concerns of immigration law and labour law, the two concepts of hyper-dependence and hyper-precarity are developed and applied through an in-depth comparative analysis of the legal and regulatory architectures of two contemporary temporary migrant workers’ programmes (TMWPs): Australia’s Temporary Work (Skilled) Subclass 457 Visa (‘457 visa’) scheme and the United Kingdom’s Tier 2 (General) visa scheme. In recent years, TMWPs in advanced industrialised countries have been touted by global and national policymakers as a desirable labour migration instrument that delivers ‘triple wins’ for host states, home states, and migrants and their families. I situate the normative concerns of the legally constructed hyper-dependence and hyper-precarity in the ethical debates on TMWPs in liberal states. I also consider how the worst extremes of the two ‘hyper’ conditions combined in highly exploitative work relations could be ameliorated, and in doing so propose some ideas for reforming key features of current TMWPs to enable migrants to exit any employment relationship and to resort to a range of voice mechanisms in the workplace.